Konsep Pembentukan Karakter dalam Pendidikan Agama Islam di Sekolah - Ayu Lestari; Erik Novianto (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
The aim of this research is to examine character education in Islamic Religious Education in Schools as well as the characters taught in Islamic Religious Education subjects in schools. This research uses a qualitative approach, namely research that produces descriptive data in the form of written words or utterances from individuals and observable behavior. The results of this research show that: First, character education in Islamic Religious Education in schools can be carried out in two ways, namely: non-lesson implementation model (through teacher example and student habits) and learning implementation model (in accordance with PAI teacher learning plans) . Second, the character education model built through non-lesson education includes: throwing rubbish in its place, praying before and after studying, diligently reciting and memorizing the Koran, greeting when meeting teachers, speaking politely, as well as being a good example of a teacher worthy of emulation. Meanwhile, character education that is built in classroom learning in Islamic Religious Education subjects includes: self-confidence, discipline, religion, and creativity.